Ellen G. White’s Prophecy According to Catholic Church View - Asep Awaludin; Elzya Husana Anik (Journal of Comparative Study of Religions (JCSR), 2020)
The term "sect" is familiar to all religious communities. This term is known not only in Islam but also in Christianity, namely Advent (Seventh-day Adventist Church). A church that keeps the Sabbath day holy was pioneered by a woman named Ellen G. White. Its doctrine and teachings are believed to be a vision from God in conflict with his prophecies, because the prophecies taught contradict the doctrine of the Catholic papacy. This research is library research (library research), using several methods including descriptive methods and critical analysis methods. This study found that Ellen G. White's prophecy is a vision from God according to Adventists. But not so with Catholics, they are aggressively looking for evidence and accusing Ellen White of being a false prophet. His claims about visions begin with great experiences in childhood. Conjecture after conjecture emerged from various sects, including the Catholic Church. Some scientists claim that his vision was a mistake because of the suffering he experienced. Finally, this research can contribute to further discussion, so that it can be used to explore the importance of understanding the prophecies of Allah's messengers to stay away from wrong thinking.